Kinetic characterization of hypophosphatasia mutations with physiological substrates - Di Mauro, S.; Manes, T.; Hessle, L.; Kozlenkov, A.; Pizauro, J. M.; Hoylaerts, M. F.; Millan, J. L. (Amer Soc Bone & Mineral Res, 2002)
We have analyzed 16 missense mutations of the tissue-nonspecific AP (TNAP) gene found in patients with hypophosphatasia. These mutations span the phenotypic spectrum of the disease, from the lethal perinatal/infantile forms to the less severe adult and odontohypophosphatasia. Site-directed mutagenesis was used to introduce a sequence tag into the TNAP cDNA and eliminate the glycosylphosphatidylinositol (GPI)-anchor recognition sequence to produce a secreted epitope-tagged TNAP (setTNAP). The properties of GPI-anchored TNAP (gpiTNAP) and setTNAP were found comparable. After introducing each single hypophosphatasia mutation, the setTNAP and mutant TNAP cDNAs were expressed in COS-1 cells and the recombinant flagged enzymes were affinity purified. We characterized the kinetic behavior, inhibition, and heat stability properties of each mutant using the artificial substrate p-nitrophenylphosphate (pNPP) at pH 9.8. We also determined the ability of the mutants to metabolize two natural substrates of TNAP, that is, pyridoxal-5'-phosphate (PLP) and inorganic pyrophosphate (PPi), at physiological pH. Six of the mutant enzymes were completely devoid of catalytic activity (R54C, R54P, A94T, R206W, G317D, and V365I), and 10 others (A16V, A115V, A160T, A162T, E174K, E174G, D277A, E281K, D361V, and G439R) showed various levels of residual activity. The A160T substitution was found to decrease the catalytic efficiency of the mutant enzyme toward pNPP to retain normal activity toward PPi and to display increased activity toward PLP. The A162T substitution caused a considerable reduction in the pNPPase, PPiase, and PLPase activities of the mutant enzyme. The D277A mutant was found to maintain high catalytic efficiency toward pNPP as substrate but not against PLP or PPi. Three mutations ( E174G, E174K, and E281K) were found to retain normal or slightly subnormal catalytic efficiency toward pNPP and PPi but not against PLP. Because abnormalities in PLP metabolism have been shown to cause epileptic seizures in mice null for the TNAP gene, these kinetic data help explain the variable expressivity of epileptic seizures in hypophosphatasia patients.
Keywords: genetic disease; missense mutations; catalytic efficiency; natural substrates; alkaline phosphatase